Anti-Modified Peptide Antibodies (AMPAs) in Rheumatoid Arthritis: Study of the Diagnostic Value of Citrullinated, Homocitrullinated, and Acetylated Fibrin/Filaggrin Chimeric Peptides - Isabel Haro; Raul Castellanos-Moreira; Raimon Sanmartí; María José Gómara (Diagnostics)
Background/Objectives. The presence of anti-citrullinated peptide/protein antibodies (ACPAs), anti-carbamylated peptide/protein antibodies (anti-CarPs), and anti-acetylated peptide/protein antibodies (AAPAs), collectively termed as anti-modified peptide/protein antibodies (AMPAs), is a hallmark of rheumatoid arthritis. These autoantibodies play a crucial role in the complex autoimmune responses observed in patients. Understanding the interplay between them is essential for early diagnosis and effective management of the disease. Methods. In this work, we investigate IgG, IgM, and IgA levels of ACPAs, anti-CarPs, and AAPAs in two cohorts: patients with established RA disease and healthy blood donors, using a unique peptide antigenic backbone. Results. Our results showed that antibody levels of anti-citrullinated peptide (CFFCP) and anti-homocitrullinated peptide (CFFHP) were significantly higher in RA patients compared to healthy blood donors in the three isotypes analyzed, IgG, IgA, and IgM. Fine specificities were more frequent when using the CFFCP antigen. Regarding the reactivity to the acetyl-lysine modified peptide (CFFAP), the correlation between IgA and IgG/IgM was very weak. CCFAP was highly specific for isotypes IgG and IgA, but its sensitivity was low for both isotypes. Anti-CarP and AAPA are significant in the context of RA, particularly concerning their IgA isotypes. Conclusions. Their inclusion in diagnostics assessments for RA, especially for anti-citrulline negative cases, presents a potential advance in the field; however, they do not replace yet traditional markers like rheumatoid factor (RF) and ACPAs.